A Compound Yarn Based Wearable Triboelectric Nanogenerator for Self‐Powered Wearable Electronics. Issue 6 (26th April 2018) - Li, Hui; Zhao, Shuyu; Du, Xinyu; Wang, Jiaona; Cao, Ran; Xing, Yi; Li, Congju
Abstract: Wearable devices such as activity tracker, digital bracelet, and smartwatch become more and more popular. However, these devices need to be charged regularly due to the limited battery capacity. Therefore, it is important to develop a method to harvest mechanical energy from human motions to drive the wearable devices. Here, a wearable triboelectric nanogenerator (WTNG) based on compound yarns, which can be integrated well with clothing due to its good breathability and flexibility, is reported. The WTNG can be mass produced owing to the low cost and process maturity. Furthermore, the WTNG exhibits outstanding flexibility, breathability, and comfortability. The WTNG can generate a maximum short‐circuit current of 4 µA, delivering an instantaneous power density of 11.0 mW m −2 to an external load. Electronic devices such as digital watch and scientific calculator can be powered by a capacitor that is charged by WTNG. This work presents a significant step toward wearable electronics and will be a widely adopted technology in the near future. Abstract : Wearable triboelectric nanogenerator (WTNG) are fabricated from a compound yarn with high comfortability and breathability to harvest the mechanical energy . The WTNG can be mass produced owing to the low cost and process maturity. Furthermore, the WTNG exhibits outstanding flexibility, breathability, and comfortability.